SPE Reservoir Simulation Symposium 1997
DOI: 10.2118/37979-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Generation EOS Compositional Reservoir Simulator: Part I - Formulation and Discretization

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractA fully implicit equation-of-state (EOS) compositional simulator for large scale reservoir simulation is presented. The simulator uses a multiblock, domain decomposition approach; that is, the reservoir is divided into non-overlapping subdomains that are solved locally in parallel (inner iteration). The subdomain grids are defined independently of each other and their connections are attained through a global interface problem (outer iteration) formulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…However, since the embedded discrete fracture model (EDFM) is developed under the EOS compositional module, we present the formulation of this module in more details. Wang et al (1997Wang et al ( , 1999 All the developments in this research, which will be presented in the forthcoming chapters, are implemented in the EOS compositional module of GPAS. Hence, in the following sections, we describe the governing equations, phase behavior equations, and solution procedure of the EOS compositional module in GPAS.…”
Section: Overview and Framework Of Gpasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the embedded discrete fracture model (EDFM) is developed under the EOS compositional module, we present the formulation of this module in more details. Wang et al (1997Wang et al ( , 1999 All the developments in this research, which will be presented in the forthcoming chapters, are implemented in the EOS compositional module of GPAS. Hence, in the following sections, we describe the governing equations, phase behavior equations, and solution procedure of the EOS compositional module in GPAS.…”
Section: Overview and Framework Of Gpasmentioning
confidence: 99%
“…Parallel processing with high performance computing clusters can alleviate these challenges to a good extent. Wang et al (1997), Zhang et al (2001), Dogru et al (2002), Gai et al (2003), andDeBaun et al (2005) demonstrated the necessity, advantages, and applicability of using parallel processing for large-scale reservoir simulations.…”
Section: Parallel Processingmentioning
confidence: 99%
“…According to Wang et al (1997), in order to describe an isothermal, multiphase/multicomponent flow in a porous medium, three types of equations are required: the material balance for all components, the phase equilibrium equations, and the equations for constraining phase saturations and component concentrations.…”
Section: Governing Equationsmentioning
confidence: 99%
“…This discrete model is solved by the IPARS (Integrated Parallel Accurate Reservoir Simulator) software developed at the Center for Subsurface Modeling at The University of Texas at Austin [10,13,19,21,[28][29][30][31]. IPARS is a parallel reservoir simulation framework for modeling multiphase, multiphysics flow in porous media.…”
Section: Mathematical Model For the Flow In An Oil Reservoirmentioning
confidence: 99%